Pengembangan Aplikasi untuk Mengukur Reusability Perangkat Lunak menggunakan Object-Oriented Metric - Arkaan Nurul Iman; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Reusability is the likelihood of segments of source code in software that can be reused to add new functionality with slight or no modification. A research conducted by Mr. Pavan Devade and Prof. Pritesh Jain in 2016 describes a method to perform reusability calculations in object-oriented programming concepts. The research explains that the class which is the main component in object-oriented programming, can be calculated for its reusability value by utilizing the object-oriented software metric, namely the CK metric. The research uses the C# programming language. Unfortunately, object-oriented programming languages ​​are not only limited to C#, Java is one of them. This study aims to develop a system that applies the reusability calculation method described by Mr. Pavan Devade and Prof. Pritesh Jain using Java programming language. This research was conducted with software engineering phase consisting of requirements analysis, system design, system implementation, and system testing. Requirements analysis produces 4 functional requirements and 1 non-functional requirement. The system design produces class diagram and 4 sequence diagrams. System implemented using Javaparser and JavaFX libraries. System is tested in three stages, namely unit testing, integration testing, and validation testing. The tests gives valid results for each stage of the test.